2018
DOI: 10.17576/mjas-2018-2202-01
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Extraction Solvents in the Dispersive Liquid-Liquid Microextraction

Abstract: Dispersive liquid-liquid microextraction (DLLME) is a novel sample preparation technique that has higher level of extraction efficiency by means of relying on microvolumes of solvents. It has gained considerable attention from researchers owing to several advantages such as its simplicity, shorter extraction time, lower cost and higher enrichment factor. In conventional DLLME, chlorinated solvents are widely used as the extraction solvents. Notwithstanding, most of these solvents are reportedly toxic and envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…High density halogenated hydrocarbon solvents such as chloroform and dichloromethane usually were used but they are highly toxic [ 38 ]. Other low-density solvents such as long-chain alcohols are suitable alternative extractants [ 39 ]. Based on preliminary experiments, it was found that long-chain alcohols such as 1-octanol, 1-decanol, 1-undecanol, and 1-dodecanol were good extractants of repaglinide (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High density halogenated hydrocarbon solvents such as chloroform and dichloromethane usually were used but they are highly toxic [ 38 ]. Other low-density solvents such as long-chain alcohols are suitable alternative extractants [ 39 ]. Based on preliminary experiments, it was found that long-chain alcohols such as 1-octanol, 1-decanol, 1-undecanol, and 1-dodecanol were good extractants of repaglinide (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate performance level, DLLME was used recently for extraction of polybrominated biphenyls in real water samples, and during 2 min of DLLME the target analytes were preconcentrated by a factor of 211–245 into 30 μL of CCl 4 . Recent reviews discuss DLLME progress in much more detail. Current research includes among others implementation of less toxic solvents, automation, hyphenation with nanoparticles, and combination of DLLME with other extractions methods such as SPE, SBSE, and supercritical fluid extraction . Experiments with less toxic solvents include hydrophobic deep eutectic solvents and diethyl carbonate .…”
Section: Liquid-phase Microextractionmentioning
confidence: 99%
“…In recent years, environmentally friendly solvents have also become attractive for the development of “green” chemistry. In this way, surfactants, low-toxic brominated and other derivates of hydrocarbons [ 26 ], deep eutectic solvents (DES) [ 27 , 28 ], ionic liquids (ILs) [ 29 ], etc., have been utilized in the developed methods to decrease toxicity of systems. On the other hand, the large-scale use of ionic liquids results in significant material costs and difficulties in understanding their mechanism of action due to the lack of studies.…”
Section: Introductionmentioning
confidence: 99%